Secuencia metodológica y el desarrollo motor en niños de la Institución Educativa Inicial Nº 847 Nuestra Señora de la Purísima, Punchana 2022 - Mera Lozano, Bertilda (2024)
With the purpose of evaluating the connection between the application of the methodological sequence and motor development in the Institución Educativa Inicial Nº847 Nuestra Señora de la Purísima Punchana 2022, a relational study was carried out with a non-experimental and correlational transectional design. The study population included all the boys and girls of the Initial Educational Institution Nº847 Nuestra Señora de la Purísima Punchana 2022, and the sample was census-based and consisted of 118 participants. Two observation guides and a survey were used to collect the data, which were validated through expert judgment. The Pearson correlation coefficient between the methodological sequence variables and motor development in children was r=0.069, which suggests a low relationship between them. Therefore, it is concluded that there is no significant connection between the application of the methodological sequence and motor development in the children of the Institución Educativa Inicial Nº847 Nuestra Señora de la Purisima Punchana 2022